Kedudukan Perempuan dalam Islam (Studi Analisis Komparatif Kitab Tafsir Nazarat fi Kitabillah dan Tafsir Al-Munir) - Adiba, Ratu; Widayati, Romlah; Safei, Abdullah (Kopertais Wilayah I DKI Jakarta dan Banten, 2025)
This research aims to examine the status of women in Islam by analyzing Qur’anic verses through a thematic exegesis (maudhu’i) approach and by comparing the interpretations of the female exegete Zainab al-Ghazali in Nazarāt fī Kitābillāh and the contemporary exegete Wahbah al-Zuhaili in Tafsīr al-Munīr. The main focus of this study is to explore how both exegetes interpret verses related to women’s roles, rights, and positions within socio-religious contexts. This study complements previous research, such as Fitriya’s thesis, which exclusively examined Zainab al-Ghazali’s perspectives on gender equality, and Suparno’s thesis, which investigated the thoughts of Muhammad Abduh and Rashid Rida in Tafsīr al-Manār. This research offers a new contribution through a comparative approach between a female and a male exegete on Qur’anic verses concerning women, thereby enriching the field of Qur’anic exegesis and gender studies. The research employs a descriptive qualitative method with a library research approach. Primary data are drawn from the two main tafsir works, while secondary data are obtained from books, scholarly articles, and other supporting literature. The analysis involves comparing both exegetes’ interpretations of ten relevant verses regarding the status of women. The findings reveal that both Zainab al-Ghazali and Wahbah al-Zuhaili emphasize the significance of women’s roles in both domestic and public spheres. However, Zainab highlights the internal struggles and resilience of women, whereas Wahbah tends to offer a more normative and textual interpretation. This study concludes that both exegetes’ thoughts remain highly relevant in addressing contemporary issues such as gender equality, social roles, inheritance rights, women’s leadership, and the persistent social stigma attached to Muslim women. These findings underscore the importance of adopting diverse exegetical approaches to understanding the Qur’anic text in a contextual and responsive manner to contemporary challenges.